2014
DOI: 10.9790/5728-10140106
|View full text |Cite
|
Sign up to set email alerts
|

On Consistency and Limitation of paired t-test, Sign and Wilcoxon Sign Rank Test

Abstract: This article investigates the strength and limitation of t-test and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
0
22
0
2
Order By: Relevance
“…Details of the code used for all tests are supplied (Appendix 1, supplemental material). The Wilcoxon test was chosen over the conventional Student t-test or Welch's t-test, because it performs better when investigating data that are not distributed normally and which have small sample sizes (Imam et al 2014).…”
Section: Quantitative Analysis Approachmentioning
confidence: 99%
“…Details of the code used for all tests are supplied (Appendix 1, supplemental material). The Wilcoxon test was chosen over the conventional Student t-test or Welch's t-test, because it performs better when investigating data that are not distributed normally and which have small sample sizes (Imam et al 2014).…”
Section: Quantitative Analysis Approachmentioning
confidence: 99%
“…The data of pretest and posttest did not own both normal distribution and same variance. Hence, the Wilcoxon signed rank test was used to analyze the data (Shan, 2014;Imam et al, 2014). The Wilcoxon test was used to analyze the differences from the observed results of two paired data.…”
Section: Resultsmentioning
confidence: 99%
“…After completing the data processing, the cleaned data's frequency Alpha, Beta, and Gamma) for each session were extracted. Each power of ea compared against the baseline's data of gamma using Wilcoxon Signed Rank tnormality assumptions (Imam, et al, 2014). SPSS ( analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Each power of ea compared against the baseline's data of gamma-band power. This comparison was carried out by -test due to the small number of samples that did not meet t normality assumptions (Imam, et al, 2014). SPSS (ver.20 for Windows) was utilized to perform the The study revealed that GBA was significantly increased in the CS compared to RS (Fig.…”
Section: (A)mentioning
confidence: 99%